Skyba M.Ye., Stechyshyn M.S., Oleksandrenko V.P., Kurskoy V.S., Martynyuk A.V. Investigation of processes of behavior nitrogen in false dispersion. - Скиба, М. Є.; Стечишин, М. С.; Олександренко, В. П.; Курской, В. С.; Мартинюк, А. В. (Problems of Tribology, 2018)
The paper presents the topics of scientific and applied researches conducted in the laboratory of the Podilskyi scientific physical-technological centre (PSPTC) at Khmelnytskyi National University. A specific feature of these investigations is that they are based on the energy theory of non-hydrogen nitriding in glow discharge (NNGD) developed in the laboratory. The latter makes it possible to control and regulate not only the regime but also the energy parameters of NNGD which greatly expands the possibilities of the influence of the existing nitriding technologies on the physical - chemical characteristics of the surface layers of metals in order to achieve the necessary performance characteristics of the hardened surfaces of machine parts. The effect of NNGD with autonomous energy nitriding regimes (current density, voltage, discharge watt-hour rating) on the surface microhardness and its distribution over the depth of the nitrided layer, the phase composition, the thickness of the nitride zone and the diffusion layer, as well as the tribological characteristics of nitrided surfaces under friction without lubrication (dry friction) are investigated on steel 40X As a result of the studies, it was determined: NNGD with autonomous saturation regimes allows to significantly reduce the energy consumption for nitriding; The unification of independent and controlled energy and regime parameters of NNGD allows to significantly expand the technological capabilities of the nitriding process in order to achieve the physical-chemical characteristics of surfaces of machine parts and equipment specified by the operating conditions; Further research, according to the authors, should be aimed at establishing relationships between volt-ampere characteristics, composition of the gas mixture and its pressure in the gas-discharge chamber.